‘Policing Schools’ Strategies: A Review of the Evaluation Evidence - Petrosino, Anthony; Guckenburg, Sarah; Fronius, Trevor (Journal of MultiDisciplinary Evaluation, 2012)
Background: Schools experience a wide range of crime and disorder, victimizing students and staff, and undermining attempts to create a safe and orderly environment for student learning. Police have long established programs with schools, but there has been no systematic review of evaluations of these programs, outside of police-led prevention classroom curriculum programs such as D.A.R.E. Purpose: This paper documents a systematic search to identify experimental and quasi-experimental evaluations that assess the effectiveness of non-educational policing strategies and programs in schools. Setting: Included studies took place in or around K-12 schools in the United States, Canada, and the United Kingdom. Intervention: Studies were included if they reported on a specific school-based strategy that heavily involved police and did not exclusively involve the police teaching a curriculum or program such as Drug Abuse Resistance Education (D.A.R.E.). Research Design: Systematic review of experimental or quasi-experimental evaluations Data Collection and Analysis: Only those impact studies that used experimental or quasi-experimental design, had at least one outcome measure of school crime or disorder, and were available through December 2009 were eligible. Electronic searches and other methods were used to identify published and unpublished evaluation reports. Findings: The searches identified a total of eleven quasi-experimental studies. Ten of the eleven studies would likely have received a “3” on the Maryland Scientific Methods Rating Scale, a common approach to classifying studies on the basis of internal validity. If evidence rating criteria from the U.S. Department of Education’s What Works Clearinghouse (WWC) were applied, only one study would likely receive a grade of “Level 2” evidence (acceptable with reservations) and the other ten studies would likely not meet WWC evidence screening criteria.